2019
DOI: 10.3112/erdkunde.2019.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Refugee Reception within a common European asylum system: looking at convergences and divergences through a local-to-local comparison

Abstract: Research on the governance of refugees has until recently remained conceptualized with the national perspective as a starting point. This article compares asylum governance at the local level between Germany, Luxembourg and the Netherlands, focusing on the often sensitive and highly debated issue of reception and accommodation. The central idea is to determine convergences and divergences of local reception structures and efforts, and how they are linked to the governance levels situated above them. Despite mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 8 publications
1
16
0
2
Order By: Relevance
“…It was a task that was better accomplished through constant and resourceful democratic support than through top-down leadership. Here our research is in line with what has been reported by recent studies on the role of municipalities in Europe: formal and informal hierarchies were re-established and the role of civil society actors was crucial (Bendel et al, 2019;Glorius et al, 2019). Even more, our research on the eight cities indicates that a strong mayor figure is only productive for urban society in a situation of acute crisis.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It was a task that was better accomplished through constant and resourceful democratic support than through top-down leadership. Here our research is in line with what has been reported by recent studies on the role of municipalities in Europe: formal and informal hierarchies were re-established and the role of civil society actors was crucial (Bendel et al, 2019;Glorius et al, 2019). Even more, our research on the eight cities indicates that a strong mayor figure is only productive for urban society in a situation of acute crisis.…”
Section: Discussionsupporting
confidence: 92%
“…The proponents of the 'local turn' literature took seriously the difficulties of generalizing research findings in these multilevel constellations and pointed to the importance of local in-depth studies (Zapata-Barrero et al, 2017). These would be able to reveal, for example, the bypassing of actors (such as the mayor) within formal and informal local hierarchies (Glorius et al, 2019). Some researchers now also started to concentrate on the role of the mayor as crucial to understanding overall local policies (Glorius et al, 2016;Haselbacher, 2019).…”
Section: Restructuring Global Urban Governance and Local Positioningsmentioning
confidence: 99%
“…First, the local and regional authorities appeared to be unprepared for this sudden influx of newcomers and struggled to find the capacity and resources to manage the reception and integration of refugees. While the federal office Bundesamt für Migration und Flüchtlinge (BAMF) is occupied with asylum procedures, regional and local authorities are responsible for the provision of housing, education and care (Glorius et al 2019 ). In 2015, the incapacity of local authorities became visible, for example, in the endless queues forming in front of the regional authority Landesamt für Gesundheit und Soziales, as well as the ‘emergency accommodations’ on the Tempelhofer field.…”
Section: The ‘Summer Of Migration’ and The Start Of Govolunteermentioning
confidence: 99%
“…The increased immigration in response to causes of flight between 2014 and 2016 has generated a number of studies with a particular focus on the arrival of people with flight biographies and the way they were dealt with and perceived in specific local contexts of the Federal Republic of Germany (including Hamann and Yurdakul, 2018;Glorius et al, 2019;Kurtenbach, 2019). Acknowledging globalised conditions and in the sense of the postmigrant point of view, however, refugee migration is to be regarded less as an exception but rather to be accepted as a status that -due to worldwide economic disparities and political power imbalances -is always an element of global mobility processes.…”
Section: Perspectives On Integration and Arrival From The Point Of View Of Migrationmentioning
confidence: 99%